Adsorption Equilibria of Dimethyl Carbonate and Ethyl Methyl Carbonate onto Activated Carbon. Issue 3 (5th February 2016) - Stehmann, Friederike; Prziwara, Paul; Bradtmöller, Christian; Schoenitz, Martin; Scholl, Stephan
Abstract: Increasing usage of lithium‐ion batteries requires new recycling strategies. Dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) represent about 50 % of the electrolyte and need to be captured from recycling exhaust gas. This study identifies adsorption as an advantageous method. Single component isotherms of DMC and EMC are presented applying the model of Tóth. Model parameters are used to calculate binary adsorption isotherms with the ideal adsorbed solution theory. Comparison with experimental data shows good agreement in respect to selectivity, temperature dependence and overall gas loading. Abstract : Recycling of lithium‐ion batteries is going to be a demanding task in the future. This contribution addresses the adsorptive cleaning of the exhaust gas produced during a recycling process by giving first equilibrium data for single and binary adsorption adsorption of electrolyte components onto activated carbon.